The relationship between the quality of school life and the school burnout - Selim Gündoğan; Hatice Özgen (Institute of Advanced Engineering and Science, 2020)
School burnout has been a research subject during recent years and is a wide case among students is associated with many factors. Among these factors, school-related concepts are remarkable. Within this study, it is aimed to investigate the relationship between school quality, school burnout and school burnout. The participant group of the study consists of a total of 364 secondary school students, 181 girls and 183 boys, whose ages are in the range of 10-15, attending various secondary schools. This sampling was determined by the maximum diversity sampling method. The data were collected with the school quality of life and school burnout scale. In the analysis of the data, correlation and structural equation model analysis were administrated. It was concluded that there is a negative relationship between school quality of life and school burnout, and that school quality of life is a negative predictor of school burnout. The results were discussed through the literature review and suggestions were made for researchers and practitioners.